ANALISIS PENGAKUAN PENDAPATAN BERDASARKAN PSAK 72 PADA PT. KAYARA MITRA SEJAHTERA (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
Revenue is an important entry in the budget report because it provides information about the organization's exhibitions and the appeal of donors through sales presentations. PSAK 72 does not require a lot of effort to implement, but it is different from other guarantors which may have a high standing and have a critical impact because the region must delay receiving funds until the handover activities are carried out. PT. Kayara Mitra Sejahtera admits that it is not difficult to implement a new system or regulation. However, it is necessary to change costs related to obligations that must be agreed upon between the two parties. So it can be concluded that PT. Kayara Mitra Sejahtera has recognized revenue in accordance with PSAK 72.